Penerapan Model Pembelajaran Collaborative Learning Berbantuan Media Poster terhadap Hasil Belajar IPS pada Siswa - Chulystiscyah, Vina; Prananosa, Ahmad Gawdy; Widaswari, Dea (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of implementing the Collaborative Learning model assisted by poster media on the Social Studies (IPS) learning outcomes of fourth-grade students at SD Negeri 43 Lubuklinggau. The research employed a quasi-experimental method using a One Group Pretest-Posttest Design. The sample consisted of all 24 students in the fourth grade, selected using a saturated sampling technique. Data collection was carried out through multiple-choice tests administered before and after the learning intervention. The results showed an improvement in students' learning outcomes after the implementation of the Collaborative Learning model assisted by poster media. This was evidenced by a significant difference between pretest and posttest scores. Based on the data analysis, it can be concluded that the Collaborative Learning model assisted by poster media is effective in enhancing Social Studies learning outcomes of fourth- grade students at SD Negeri 43 Lubuklinggau. Keywords: Collaborative Learning, Poster Media, Learning Outcomes, Social.